Songket Industry Wastewater Processing Using Electrocoagulation Method - Rusdianasari Rusdianasari; Ibnu Hajar; Indri Ariyanti (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
The increment of Songket popularity as the traditional fabric from South Sumatra increases the production of Songket and the wastewater produced during the dying process. The dying process produces the reddish wastewater, and if it is disposed of directly into the environment, it will have a negative impact on the waters. The wastewater treatment of this reddish liquid is by electrocoagulation method. Electrocoagulation method is contaminants removal by electrical and chemical treatment system. The electrocoagulation method in this research was conducted in a batch where the wastewater was treated using 16.5 x 7.0 x 0.2 cm aluminum electrode. The parameters varied were the current density and processing time to determine the pH value, color intensity, BOD5, COD, TSS, and phenol levels. The optimum condition obtained from this study at a current density of 25 A/m2 with a processing time of 160 minutes. The effectiveness of Songket wastewater electrocoagulation was 67.28% for TSS, 54.13% for BOD5, 63.64% for COD, color intensity 79.21% and phenol content of 74.93% respectively. The result has fulfilled the quality standard of textile industry wastewater treatment.